2019
DOI: 10.1590/0104-1428.05617
|View full text |Cite
|
Sign up to set email alerts
|

Natural ageing of polyaramide fiber from ballistic armor

Abstract: Ballistic armor has been manufactured primarily based on polyaramide (Kevlar and Twaron) or Dyneema but the lifespan warranty in Brazil is only 5 years and after this time period they are incinerated or comminuted and ground up. This study aims to evaluate the changes on the physical, mechanical and morphological properties of polyaramide fibers of ballistic armor after natural aging. These samples with different fabrication (2005 and 2010) and usage time were exposed to natural weathering in the city of Porto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Cordeiro Konarzewski et al 37 and Moure et al 38 respectively found that the changes in physical, mechanical, and morphological properties, as well as weight and density of fibers and types of fabrics, would affect the degree of degradation of body armor made of aramids after natural aging. At low impact energies, the energy absorption capacity of aramid sheets is greater than that of thick plates.…”
Section: Empirical and Analyticalmentioning
confidence: 99%
“…Cordeiro Konarzewski et al 37 and Moure et al 38 respectively found that the changes in physical, mechanical, and morphological properties, as well as weight and density of fibers and types of fabrics, would affect the degree of degradation of body armor made of aramids after natural aging. At low impact energies, the energy absorption capacity of aramid sheets is greater than that of thick plates.…”
Section: Empirical and Analyticalmentioning
confidence: 99%
“…Additionally, ballistic vests, manufactured based on high-performance polymers, have an expiration date fixed from the date of manufacture, and must be permanently disposed of or destroyed after this period, causing financial loss to the country [ 30 , 31 ]. The materials presented in this article have already been studied with a proposal for partial replacement of the common ballistic panel [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…These fibers, with a low elongation at break and a high modulus of elasticity, are especially useful in areas that require high resistance to impact forces and abrasion, such as armor and personal protective equipment, cables, ropes, boat rigging, and parachutes. Unfortunately, most para-aramid fibers are sensitive to the effects of UV radiation, exposure to which results in visible changes to their natural color and decreases the long-lasting strength of the fibers [ 14 ]. Moreover, they are also characterized by high moisture absorption.…”
Section: Introductionmentioning
confidence: 99%